Cash waqf deposit account in Islamic Banks – a proposed banking product / Assoc. Prof. Dr Lahsasna Ahcene - Ahcene, Assoc. Prof. Dr Lahsasna (2013)
Purpose: The main objective of this paper is to propose a deposit account to the Islamic bank based on the cash waqf model in order to be part of the banking business operations, and deposit banking structure. The paper includes a discussion on the Shariah rules governing the management of the account of the cash waqf to ensure the Shariah compliance in carrying out business activities of the cash waqf account. The cash waqf account model is meant to develop and enhance the Islamic finance industry in particular, and realize the public benefit of the Umma at large. Cash waqf can be used to enhance and facilitate the financial needs in the market place and participate positively to the growth of the Muslim economy globally. The cash waqf account model presented in this paper is based on the banking operation model; therefore the concern is to elaborate on its operation aspects in the banking system.